2019
DOI: 10.7287/peerj.preprints.27796v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The complete chloroplast genome of the Jerusalem artichoke (Helianthus tuberosus L.) and an adaptive evolutionary analysis of the ycf2 gene

Abstract: Jerusalem artichoke (Helianthus tuberosus L.) is widely cultivated in Northwest China which has become an emerging economic crop with rapid development. Because of its elevated inulin content and high resistance, it is widely used in functional food, inulin processing, feed, and ecological management. In this study, Illumina sequencing technology was utilized to assemble and annotate the complete chloroplast genome sequences of Jerusalem artichoke. The total length was 151,431 bp, including four conserved regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In addition, Watsonia longifolia and Gladiolus communis exhibited significant inversions from petN to trnE-UUC (approximately 3 kb) (Figure 2). In many studies, ycf2 gene alone provides well-supported phylogeny because of its large size and extensive sequence variation (containing many INDELS) uniquely shared by some species and is frequently employed in phylogenetic research on angiosperms (Huang et al, 2010;Zhong et al, 2019;Tang et al, 2022). Our findings revealed significant deletions and inconsistent variations in the ycf2 gene region.…”
Section: Pseudogenization and Inversionsmentioning
confidence: 66%
See 2 more Smart Citations
“…In addition, Watsonia longifolia and Gladiolus communis exhibited significant inversions from petN to trnE-UUC (approximately 3 kb) (Figure 2). In many studies, ycf2 gene alone provides well-supported phylogeny because of its large size and extensive sequence variation (containing many INDELS) uniquely shared by some species and is frequently employed in phylogenetic research on angiosperms (Huang et al, 2010;Zhong et al, 2019;Tang et al, 2022). Our findings revealed significant deletions and inconsistent variations in the ycf2 gene region.…”
Section: Pseudogenization and Inversionsmentioning
confidence: 66%
“…Members of the Crocoideae, Nivenioideae, and Aristeoideae subfamilies shared a 237-bp deletion in the ycf2 gene (Supplementary Figure S1) as we moved from the basal (Isophysioideae) to the higher clade (Crocoideae, Nivenioideae, and Aristeoideae) (Figure 6). Zhong et al (2019) performed selective locus detection of the ycf2 gene in eight species of the composite family and reported that the ycf2 gene has undergone adaptive evolution. Hu et al (2015); Fan et al (2018); Zhong et al (2019), andWu et al (2020) investigated the positive selection of the protein-coding ycf2 gene and reported its role in adaptation to diverse ecosystems.…”
Section: Gene Locus Deletion In Ycf2 Genementioning
confidence: 99%
See 1 more Smart Citation
“…The ycf2, psbI-trnG, ndhA-ndhI, psbZ-trnG, rps12-ndhB, rpl33-rpoA, rpoA-psbB and rpoC1 regions were revealed as mutational hotspots of six Shorea species with two Parashorea species in this study. Among the mutational hotspot region, ycf2, psbI-trnG, psbZ-trnG has been found to have the highest degree of differentiation and hence can be utilised to investigate adaptive evolution traits of the gene [33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…ycf2 has become a useful gene for assessing sequence variation and evolution in plants [40]. Positive selection of ycf2 was also found to be involved in adaptation in other species [41]. However, due to the extremely high Ka/Ks value ( =231.51421) and unknown function, ycf2 is a valuable resource for future research of the adaptive evolution of Chrysosplenium.…”
Section: Discussionmentioning
confidence: 99%